Central African Republic : Technical Assistance Report-Governance Diagnostic Report. (IMF Staff Country Reports; Country Report, 2021)
The gradual return to peace in the Central African Republic (CAR) promises stronger and more equitable growth. Nonetheless, the country faces serious constraints with a security situation that remains vulnerable and an economy in the throes of reconstruction, including in terms of the government's administrative capacities. These constraints are reflected in problems of governance and greater vulnerability to corruption, and they find a favorable breeding ground in the country's weak capacities and result in resource allocations and uses that are sometimes inadequate. The authorities are aware of these weaknesses, and they have emphasized a national strategy to fight corruption, and more generally, to improve governance as a factor of development.